Endothelin B receptor immunodynamics in pulmonary arterial hypertension - Tabeling, Christoph; González Calera, Carla R.; Lienau, Jasmin; Höppner, Jakob; Tschernig, Thomas; Kershaw, Olivia; Gutbier, Birgitt; Naujoks, Jan; Herbert, Julia; Opitz, Bastian; Gruber, Achim D.; Hocher, Berthold; et al. (Frontiers in immunology, 2022)
IntroductionInflammation is a major pathological feature of pulmonary arterial hypertension (PAH), particularly in the context of inflammatory conditions such as systemic sclerosis (SSc). The endothelin system and anti-endothelin A receptor (ETA) autoantibodies have been implicated in the pathogenesis of PAH, and endothelin receptor antagonists are routinely used treatments for PAH. However, immunological functions of the endothelin B receptor (ETB) remain obscure.MethodsSerum levels of anti-ETB receptor autoantibodies were quantified in healthy donors and SSc patients with or without PAH. Age-dependent effects of overexpression of prepro-endothelin-1 or ETB deficiency on pulmonary inflammation and the cardiovascular system were studied in mice. Rescued ETB-deficient mice (ETB-/-) were used to prevent congenital Hirschsprung disease. The effects of pulmonary T-helper type 2 (Th2) inflammation on PAH-associated pathologies were analyzed in ETB-/- mice. Pulmonary vascular hemodynamics were investigated in isolated perfused mouse lungs. Hearts were assessed for right ventricular hypertrophy. Pulmonary inflammation and collagen deposition were assessed via lung microscopy and bronchoalveolar lavage fluid analyses.ResultsAnti-ETB autoantibody levels were elevated in patients with PAH secondary to SSc. Both overexpression of prepro-endothelin-1 and rescued ETB deficiency led to pulmonary hypertension, pulmonary vascular hyperresponsiveness, and right ventricular hypertrophy with accompanying lymphocytic alveolitis. Marked perivascular lymphocytic infiltrates were exclusively found in ETB-/- mice. Following induction of pulmonary Th2 inflammation, PAH-associated pathologies and perivascular collagen deposition were aggravated in ETB-/- mice.ConclusionThis study provides evidence for an anti-inflammatory role of ETB. ETB seems to have protective effects on Th2-evoked pathologies of the cardiovascular system. Anti-ETB autoantibodies may modulate ETB-mediated immune homeostasis.
Gesehen am 06.02.2024